Pengaruh Penguatan Positif Berdasarkan Teori Behavioristik terhadap Disiplin Belajar Siswa di Madrasah Ibtidaiyah Najmul Falah Bandung - Zaki Mubarok; Syarifah Aini Kamilah; Khoirudin Miftah (At Turots: Jurnal Pendidikan Islam, 2026)
This study examines the effect of positive reinforcement based on behaviorist theory on students’ learning discipline at Madrasah Ibtidaiyah Najmul Falah Bandung, an Islamic elementary school that emphasizes both academic and moral development. The background of this study arises from the growing concern over the decline in students’ learning discipline, which is reflected in irregular attendance, incomplete assignments, and lack of focus during lessons. To address this issue, the research applies B.F. Skinner’s Behaviorist Theory (1953), which posits that behavior can be shaped and strengthened through reinforcement. The study employed a quantitative approach using an ex post facto design, involving 60 students selected from a population of 130 through proportionate stratified random sampling. Data were collected through questionnaires, classroom observations, interviews, and documentation, then analyzed using SPSS version 25 with normality, homogeneity, and independent sample t-test analysis. The results of the t-test revealed a significance value of 0.461 (p > 0.05), indicating no statistically significant difference in learning discipline between students who received positive reinforcement and those who did not. However, descriptive findings suggest that positive reinforcement contributes positively to students’ motivation, attentiveness, and engagement in classroom activities. These findings align with Skinner’s behaviorism while complementing Bandura’s social learning perspective and Lickona’s (1991) character education model, emphasizing that long-term learning discipline cannot rely solely on external reinforcement but must be supported by internal motivation, teacher modeling, and consistent value-based practices. The study concludes that positive reinforcement plays a supportive yet important role in enhancing students’ learning discipline, particularly when integrated into holistic Islamic education that nurtures both cognitive achievement and moral-spiritual growth.